Changes of Ictal-Onset Epileptic Network Synchronicity in Childhood Absence Epilepsy: A Magnetoencephalography Study - Sun, Yulei; Li, Yihan; Shi, Qi; Wu, Caiyun; Sun, Jintao; Chen, Qiqi; Hu, Zheng; Xiang, Jing; Wang, Xiaoshan (Frontiers in Neurology, 2020)
ABSTRACT Objective: To further understand the mechanisms underlying epileptic network and the characteristics of individual specific network, we conducted a study on brain network by magnetoencephalography (MEG) with a focus on patients with childhood absence epilepsy (CAE). Methods: The network connectivity of 22 patients was investigated with MEG at the source level. Network connectivity of spikes and slow waves was computed with Accumulated source imaging (ASI) and correlation analysis. Time-frequency analysis was used to characterize the network changes during the ictal-onset period of each patient and the potential factors which caused it. Results: We found that spectral power increased at around 1 s and distributed at 2-4 Hz in all patients. Ictal spikes simultaneously showed elevation of network connectivity, which was predominantly excitatory connections, when generalized firing activity spread to the overall brain. High frequency oscillations (HFOs) were prone to detect overexcited neuronal firing in certain focal areas. Conclusions: Personal network changes during ictal onset had unique features in time range and parallel seizure rhythm uniformly in every patient. There was an important time point for generalized discharges of epileptic network. Ictal spiking activity played an important role in the epileptic network synchronicity of CAE. Frequency oscillations provided references for locating abnormal changes in neuromagnetic signals.